Que le pasa a Timmy? - Shriver, Maria; Speidel, Sandra (Warner Books y Little, Brown, 2001)
Making friends with a mentally retarded boy helps Kate learn that the two of them have a lot in common.
Keywords: Retrasados mentales -- Novela juvenil; Amistad -- Novela juvenil